Food systems transformation would reshape global agriculture - Matthew Gibson; Marina Sundiang; Daniel Mason-D’Croz; Thais Diniz Oliveira; Felicitas Beier; Lauren Benavidez; Astrid Bos; Maksym Chepeliev; Jonathan Doelman; Shahnila Dunston; Shinichiro Fujimori; Tomoko Hasegawa; et al. (Nature, 2026)
Abstract Food systems are a major contributor to exceeding planetary boundaries 1–3 and poor quality diets are a key mortality risk globally 4 . Projected population and income growth could exacerbate these challenges 5 . In response, there are calls for transformation towards healthy and sustainable food systems 6–8 . However, the scale and distribution of the impacts of this transformation on agriculture are underexplored. Here we show that, by 2050, the transformation of food systems towards healthy diets (adoption of the EAT– Lancet reference diet), improved productivity and halving of food waste results in a fundamental restructuring of global agriculture, aspects of which break with historical trends. Scenario simulations using a multimodel ensemble of ten global economic models show a 6% median decrease in agricultural land (+1% to −26%) compared with 2020 levels. By 2050, agricultural production would be 17% lower than business-as-usual projections (−2% to −32%) and, economically, the value of this production is US$1.6 trillion (26%) lower (+8% to −58%). Within this, the value of livestock production would be substantially lower than current 2050 projections (−49% to −83%), while vegetable, fruit, nut and legume production value would increase by 23% (−33% to +106%). Results are dependent on the assumed policies to achieve the transformation scenario. We highlight a more active role for food policy to consider the benefits of such a transformation (improved population health and reduced environmental pressures) and navigate the political economy of its impacts.